2007
DOI: 10.1111/j.1365-2761.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus isolation vs RT‐PCR: which method is more successful in detecting VHSV and IHNV in fish tissue sampled under field conditions?

Abstract: This study compared the results of reverse transcription-polymerase chain reaction (RT-PCR) and traditional virus isolation on cell culture in detection of viral haemorrhagic septicaemia virus (VHSV) and infectious haematopoietic necrosis virus (IHNV). RT-PCR was used for 172 tissue sample pools (total of 859 fish) originating from a field survey on the occurrence of VHSV and IHNV in farmed and wild salmonids in Switzerland. These samples represented all sites with fish that were either identified as virus-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…As in the present study an increased number of positive pooled samples (n = 4) were found using RT-PCR compared to cell culture isolation. Experimental testing of the sensitivity of cell culturing versus PCR-methodology has demonstrated RT-PCR the most sensitive [51], [52]. The development of PCR assays with higher sensitivity and a broader detection range to several genotypes of VHSV has made this the preferred method for VHSV detection in most laboratories [36].…”
Section: Discussionmentioning
confidence: 99%
“…As in the present study an increased number of positive pooled samples (n = 4) were found using RT-PCR compared to cell culture isolation. Experimental testing of the sensitivity of cell culturing versus PCR-methodology has demonstrated RT-PCR the most sensitive [51], [52]. The development of PCR assays with higher sensitivity and a broader detection range to several genotypes of VHSV has made this the preferred method for VHSV detection in most laboratories [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the unstable nature of RNA and the risk of contamination, Knüsel et al (2007) suggested that RT-mPCR is more suitable for laboratory samples instead of testing on field samples. Consequently, in this study, we developed an RT-mPCR method with commonly used RT-PCR kits for the detection of VHSV and IPNV.…”
Section: Discussionmentioning
confidence: 99%
“…However, these assumptions depend on the prevalence of the infectious agent in the source population and the concentration of target analyte in each specimen included in the pool (Johnson et al, ; Zainathan, Carson, Crane, & Nowak, ). In low prevalence scenarios, pools of tissues or swabs from non‐infected animals can dilute an already low concentration of an infectious agent that may be close to the detection limit or cut‐off value used to classify a test result as positive or negative (Corsin et al, ; East, ; Jansen et al, ; Johnson et al, ; Knüsel et al, ; Oidtmann et al, ). Another important factor that is often driven by prevalence and affected by analyte concentration is the number of positives per pool.…”
Section: Recommended Criteria For Pooling Samplesmentioning
confidence: 99%